Implementasi Alokasi Dana Desa dalam Pemberdayaan Masyarakat Di Desa Mudung Darat Kecamatan Maro Sebo Kabupaten Muaro Jambi - Masriyani Masriyani; Hisbah Hisbah; Feri Setiawan (Wajah Hukum, 2021)
According to the results of observations made by the author in the village of Mudung Darat, Maro Sebo District, Muaro Jambi Regency, the management of village funds, especially the Village Fund Allocation, has not been implemented optimally, especially in the planning and implementation stages of the village fund allocation. This study aims to determine and analyze the Implementation of Village Fund Allocation in Community Empowerment in Mudung Darat Village, Muaro Jambi Regency, to identify and analyze the constraints of Village Fund Allocation Implementation in Community Empowerment in Mudung Darat Village, Muaro Jambi Regency and to identify and analyze the efforts made to overcome the obstacles in implementing Village Fund Allocation in Community Empowerment in Mudung Darat Village, Muaro Regency. This type of research used in this paper is empirical juridical research. The implementation of ADD in carrying out Public Expenditures and community empowerment has not been carried out optimally. The obstacles faced in implementing the allocation are the lack of understanding of the Village Government apparatus regarding the main tasks and functions and the lack of information and socialization to the community. Quality of Human Resources (HR) That Has Not Supported the Management and Implementation of Village Fund Allocation. The culture of mutual cooperation among the people of Mudung Darat Village is starting to fade, and the culture of mutual cooperation is the hallmark of a village.